Measurement of the accuracy of dental working casts using a coordinate measuring machine - Potran, Michal; Štrbac, Branko Mile; Puškar, Tatjana; Hadžistević, Miodrag; Hodolič, Janko; Trifković, Branka (Vojnosanitetski pregled, 2017)
Background/Aim. Dental impressions present a negative imprint of intraoral tissues of a patient which is, by pouring in gypsum, transferred extraorally on the working cast. Casting an accurate and precise working cast presents the first and very important step, since each of the following stages contributes to the overall error of the production process, which can lead to inadequately fitting dental restorations. The aim of this study was to promote and test a new model and technique for in vitro evaluation of the dental impression accuracy, as well as to asses the dimensional stability of impression material depending on the material bulk, and its effect on the accuracy of working casts. Methods. Impressions were made by the monophasic technique using the experimental master model. Custom trays with spacing of 1, 2 and 3 mm were constructed by rapid prototyping. The overall of 10 impressions were made with each custom tray. Working casts were made with gypsum type IV. Measurement of working casts was done 24 h later using a coordinate measuring machine. Results. The obtained results show that the working casts of all the three custom trays were in most cases significantly different in the transversal and sagittal planes in relation to the master model. The height of abutments was mainly unaffected. The degree of convergence showed certain significance in all the three custom trays, most pronounced in the tray with 3 mm spacing. Conclusion. The impression material bulk of 1–3 mm could provide accurate working casts when using the monophasic impression technique. The increase of the distance between abutment teeth influences the accuracy of working casts depending on the material bulk.